Intention To Use Mobile Banking Application: Empirical Evidence From Indonesia - Verawati, Liesta; Syaeful Anwar, Muhamad; Afiati, Lely (The International Journal of Business Review (The Jobs Review), 2024)
Purpose – The study aims to examine the factors that influence the intention to use mobile banking in Indonesia, specifically focusing on perceived usefulness, trust, and perceived security.Design/methods/approach – The research employs an explanatory design with a quantitative approach. Data were collected through a self-administered survey method using online questionnaires. The sample consisted of 115 respondents who use mobile banking applications. The data were analyzed using PLS-SEM (Partial Least Squares Structural Equation Modeling) with the software SmartPLS 3.3.Findings – The study reveals that perceived usefulness is the strongest predictor of the intention to use mobile banking applications among users. This means that the more beneficial users find mobile banking, the more likely they are to intend to use it. Trust also plays a significant positive role in influencing the intention to use mobile banking, suggesting that users are more inclined to adopt mobile banking if they trust the service provider. On the other hand, perceived security does not have a significant impact on the intention to use mobile banking. The research model accounts for 62% of the variance in the intention to use mobile banking, indicating that other factors not included in the study might also play a role.Research implications/limitations – Mobile banking providers should enhance the perceived usefulness and trustworthiness of their services to increase user adoption. The study's limitations include its small sample size and geographic focus on Indonesia, which may affect the generalizability of the findings. Further research with a broader and more diverse sample is recommended.Originality/value – This study contributes to the understanding of mobile banking adoption in Indonesia by providing empirical evidence on the importance of perceived usefulness and trust over perceived security in influencing user intention.